2017
DOI: 10.1007/s00380-017-1092-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of right ventricular distensibility on congestive heart failure with preserved left ventricular ejection fraction in the elderly

Abstract: To elucidate involvement of age-related impairments of right ventricular (RV) distensibility in the elderly congestive heart failure (CHF), we examined the prevalence of less-distensible right ventricle in patients with preserved left ventricular ejection fraction (LVEF) over a wide range of ages. In 893 patients aged from 40 to 102 years, we simultaneously recorded electrocardiogram, phonocardiogram, and jugular venous pulse wave. Using signal-processing techniques, the prominent 'Y' descent of jugular pulse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 36 publications
1
28
0
1
Order By: Relevance
“…In our previous study, DT of mitral early flow was prolonged before the increase in the incidence of a less-distensible right ventricle and elevated RV systolic pressure. 7 Our previous data also support that a lessdistensible right ventricle often originates from elevated RV afterload associated with LV diastolic dysfunction. Elevated LV filling pressure itself may directly influence RV Table 1 Contingency table for evaluation of RV distensibility Cardiologist B Distensible right ventricle Less-distensible right ventricle Totals Cardiologist A Distensible right ventricle 193 3 196 Less-distensible right ventricle 1 125 126 Totals 194 128 322 Prominent 'Y' descent and a poorer prognosis in HFpEF Data are number of patients (%), median (interquartile range), or mean ± SD.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…In our previous study, DT of mitral early flow was prolonged before the increase in the incidence of a less-distensible right ventricle and elevated RV systolic pressure. 7 Our previous data also support that a lessdistensible right ventricle often originates from elevated RV afterload associated with LV diastolic dysfunction. Elevated LV filling pressure itself may directly influence RV Table 1 Contingency table for evaluation of RV distensibility Cardiologist B Distensible right ventricle Less-distensible right ventricle Totals Cardiologist A Distensible right ventricle 193 3 196 Less-distensible right ventricle 1 125 126 Totals 194 128 322 Prominent 'Y' descent and a poorer prognosis in HFpEF Data are number of patients (%), median (interquartile range), or mean ± SD.…”
Section: Discussionsupporting
confidence: 75%
“…6 Deterioration of RV afterload may cause RV diastolic dysfunction, resulting in a lessdistensible right ventricle. 7 Olivetti et al found that aging was accompanied by a decrease in myocyte nuclei of 14 million/year and an increase in reactive cellular hypertrophy of the right ventricle. 7 Our previous data also support that a lessdistensible right ventricle often originates from elevated RV afterload associated with LV diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations